(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
This paper deals with a geochemical study of radioactive elements (uranium, thorium, and potassium) in rocks of different composition within the Latakia sheet, where the concentration of radioactive isotopes 238U, 232 Th, 40K was determined using a high-purity germanium detector, and an X-ray diffraction method-was (XRD) used to determine the mineral phases. The study showed a variation in the concentration of 238U, 232 Th, and 40K in the rocks of the study area, and it was observed that the radioactivity is mainly related to the element thorium, due to the presence of metals carrying thorium. The low concentration of potassium in most samples is due to the low percentage of mica and feldspar metals, or their corruption to elite and montmorillonite. The ratio Th/U indicated a suitable reference environment for deposition of uranium in most sedimentary samples, and this high percentage in the ophiolitic complex samples (with the exception of serpentinite rocks) is due to the oxidation and migration of uranium from these rocks towards rocks of sedimentary formations, and the stability of thorium and is not affected by oxidative conditions. The ratio Th/K indicated the predominance of elite and montmorillonite in most samples, with the presence of weather-resistant thorium-bearing metals in the basalt sample, and the sediments of Lake 16 October. The mineralogical study revealed the existence of mineral phases of uranium and thorium, in addition minerals carrying radioactive elements such as monazite and zircon